Exosomes in pathogenesis, diagnosis, and treatment of pulmonary fibrosis - Yang, Yang; Liu, Yufei; Chai, Yilu; Liu, Ke; Hu, Wei; Zhao, Keni; Zhu, Yi; Gao, Peiyang; Huang, Qingsong; Zhang, Chuantao (Frontiers in Pharmacology, 2022)
Pulmonary fibrosis (PF) is a group of interstitial lung diseases that seriously endanger human life and health. Despite the current advances in research on the pathogenesis and treatment of PF, the overall quality of survival and survival rates of PF patients remain low, prompting the search for more effective therapeutic approaches. Exosomes are nanoscale vesicles with diameters ranging from approximately 30 to 150 nm, capable of transporting a variety of molecules in the body and mediating intercellular communication. There is an increasing number of studies focusing on the role of exosomes in PF. This review demonstrates the significance of exosomes in the pathogenesis, diagnosis, and treatment of PF. Exosomes are able to influence inflammatory, immune, and extracellular matrix deposition processes in PF and regulate the corresponding cytokines. Some exosomes detected in sputum, blood, and bronchoalveolar lavage fluid may be used as potential diagnostic and prognostic biomarkers for PF. Exosomes derived from several cells, such as mesenchymal stem cells, have demonstrated potential as PF therapeutic agents. Drug delivery systems using exosomes may also provide new insights into PF therapy.